The Influence of Employee Performance and Budget Management on the Quality of Financial Reports with the Implementation of Internal Control as a Moderating Variable at Mulawarman University - Apriati Uleh; Set Asmapane; Ledy Setiawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The quality of financial reporting at Universitas Mulawarman is influenced by various factors, including employee performance and budget management, which often face challenges such as recording errors and budget discrepancies. This study aims to analyze the influence of employee performance and budget management on the quality of financial reporting, with internal control implementation as a moderating variable. Using a quantitative approach, data were collected through questionnaires from 71 respondents involved in the university’s financial management and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that employee performance and budget management have a positive and significant impact on the quality of financial reporting. However, internal control implementation does not significantly moderate the relationship between employee performance and budget management with financial reporting quality, suggesting that the direct effects of these factors are sufficiently strong. The study’s implications recommend that the university enhance technical training for employees, strengthen budget planning, and refine internal control procedures to support accountability and transparency in financial reporting.